Adaptação de um livro impresso para iPad - Will, Fernanda Lianna (2013)
This graduation work presents the adaptation of a printed theatre play for digital devices. Also in this work is shown the development of the interface to compound a application for iPad, and digital animations for the cover and acts of the play.